The Interaction Between Gaze and Facial Expression in the Amygdala and Extended Amygdala is Modulated by Anxiety - Ewbank, Michael P. (Frontiers Research Foundation, 2010)
Behavioral evidence indicates that angry faces are seen as more threatening, and elicit greater anxiety, when directed at the observer, whereas the influence of gaze on the processing of fearful faces is less consistent. Recent research has also found inconsistent effects of expression and gaze direction on the amygdala response to facial signals of threat. However, such studies have failed to consider the important influence of anxiety on the response to signals of threat; an influence that is well established in behavioral research and recent neuroimaging studies. Here, we investigated the way in which individual differences in anxiety would influence the interactive effect of gaze and expression on the response to angry and fearful faces in the human extended amygdala. Participants viewed images of fearful, angry and neutral faces, either displaying an averted or direct gaze. We found that state anxiety predicted an increased response in the dorsal amygdala/substantia innominata (SI) to angry faces when gazing at, relative to away from the observer. By contrast, high state anxious individuals showed an increased amygdala response to fearful faces that was less dependent on gaze. In addition, the relationship between state anxiety and gaze on emotional intensity ratings mirrored the relationship between anxiety and the amygdala/SI response. These results have implications for understanding the functional role of the amygdala and extended amygdala in processing signals of threat, and are consistent with the proposed role of this region in coding the relevance or significance of a stimulus to the observer.